SEQUENTIAL APPLICATION OF CAREGIVER TRAINING TO IMPLEMENT PEDIATRIC FEEDING PROTOCOLS. (11th December 2012) - Pangborn, Meghan M.; Borrero, Carrie S. W.; Borrero, John C.
<x xml:space="preserve">Abstract</x> The purpose of this study was to evaluate the effectiveness of current caregiver training practices by implementing training components sequentially, to teach parents mealtime protocols. A multiple baseline design was implemented across two caregiver dyads. Therapist‐fed meals were conducted prior to training to identify an effective intervention to increase food acceptance and decrease food refusal. The package consisted of seven components: observation, written and verbal protocol review, video review, structured observation, modeling, role play, and immediate feedback. Correct implementation of mealtime protocols, by caregivers, were evaluated throughout the training process by having caregivers conduct meal sessions following each training component to determine if additional training was necessary. Results showed that the training procedures were effective in teaching caregivers to implement mealtime protocols, and systematic introduction of the training components produced systematic and incremental changes in correct caregiver implementation. In addition, all participants completed training without requiring all seven training components. Copyright © 2012 John Wiley & Sons, Ltd.